Altered ligands reveal limited plasticity in the T cell response to a pathogenic epitope - Pingel, S; Launois, P; Fowell, D J; Turck, C W; Southwood, S; Sette, A; Glaichenhaus, N; Louis, J A; Locksley, R M (The Journal of experimental medicine, 1999)
Experimental leishmaniasis offers a well characterized model of T helper type 1 cell (Th1)-mediated control of infection by an intracellular organism. Susceptible BALB/c mice aberrantly develop Th2 cells in response to infection and are unable to control parasite dissemination. The early CD4(+) T cell response in these mice is oligoclonal and reflects the expansion of Vbeta4/ Valpha8-bearing T cells in response to a single epitope from the parasite Leishmania homologue of mammalian RACK1 (LACK) antigen. Interleukin 4 (IL-4) generated by these cells is believed to direct the subsequent Th2 response. We used T cells from T cell receptor-transgenic mice expressing such a Vbeta4/Valpha8 receptor to characterize altered peptide ligands with similar affinity for I-Ad. Such altered ligands failed to activate IL-4 production from transgenic LACK-specific T cells or following injection into BALB/c mice. Pretreatment of susceptible mice with altered peptide ligands substantially altered the course of subsequent infection. The ability to confer a healer phenotype on otherwise susceptible mice using altered peptides that differed by a single amino acid suggests limited diversity in the endogenous T cell repertoire recognizing this antigen.